TINDAKAN HUKUM PEMERINTAH DALAM TATA KELOLA PENANGANAN PENGUNGSI DARI LUAR NEGERI DI PEKANBARU TAHUN 2022 - Yan’Auti, Feny; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
A government action or deed is an action or legal action carried out by the government in order to carry out government functions and duties. The functions and tasks of government are very broad and complex so that government actions or legal acts become diverse and complex. International Refugees are people who experience a well-founded fear of persecution for reasons of race, religion, nationality, membership of a particular social group, or political Opinion who are outside their country and are targets of persecution. the Pekanbaru City Government and UNHCR must of course take correct action in handling refugees from abroad in Pekanbaru. This treatment is needed to ensure their quality of life while they are refugees in Pekanbaru City. The method used for this research is a descriptive method with qualitative methods. The types of data for this research are primary data and secondary data. The data analysis technique used is qualitative descriptive data technique. By using the theory of Government Action according to Aminuddin Ilmar, namely planning, administration and licensing, funding. The results of this research are that the governance carried out by the Pekanbaru City government towards refugees from abroad has been carried out optimally following the directions in Presidential Regulation No. 125 of 2016 concerning Handling of Refugees from Abroad. However, there are several obstacles starting from the SOP regarding handling refugees which is not yet optimal, violations committed by refugees such as riding and owning motorbikes without a driving license, as well as demonstrations which are carried out repeatedly with the aim of being immediately transferred to a third country, asking for permission. to work in the Pekanbaru City area. Keywords: Overseas Refugees, Government Actions, Government Governance